(untitled) - Erickson, Carolly (New Jersey, 2005)
In the early 1790s, Botany Bay prisoner Mary Bryant, her husband William, her two small children, and seven other convicts stole a boat and escaped Sydney by sailing all the way north to Timor, some 3250 treacherous miles in under ten weeks, an incredible nautical achievement. There they passed themselves off to the local Dutch governor as the survivors of a shipwreck. After a couple of months, however, William spilled the beans and the governor locked them up. Soon they found themselves on the way back to England in irons. William and Mary's youngest died in the fever port at the end of the first leg of the journey. Three of the prisoners died on the next leg. Mary's remaining child died on the third. Mary's future looked grim upon her return to London: she would likely be sent back to Australia, but after surviving such impossible rigors she became a cause celebre instead, dubbed by the English press The Girl From Botany Bay and championed by James Boswell. Ultimately, she would be pardoned.
Keywords: Thieves,Women prisoners,Exiles,Những tên cướp; England,Cornwall (County),Australia,Botany Bay (N.S.W.),Nước Anh